Analysis of the impact of the SARS-CoV-2 infection on the pediatric population hospitalized during the pandemic in the Greater Paris University Hospitals - Semeraro, Michaela; Pinson, Pierre; Populaire, Margaux; Dellagi, Mourad; Oualha, Mehdi; Beeker, Nathanael; Chappuy, Hélène (Frontiers in Pediatrics, 2023)
Background The clinical characteristics, disease progression and outcome in children affected by Coronavirus-2019 (COVID-19) infection appear significantly milder compared to older individuals. Nevertheless, the trends in hospitalization and clinical characteristics in the pediatric population seem to be different over time across the different epidemic waves. Objective To understand the impact of the different COVID-19 variants in the pediatric population hospitalized in the Pediatric Departments of the Public Hospital in the Greater Paris area by the analysis performed with the Assistance Publique-Hopitaux de Paris (AP-HP) Health Data Warehouse. Results In the period between January 2020 and March 2022, 9163 pediatric patients with COVID-19 infection were hospitalized in 21 APHP hospitals. The number of patients with COVID-19 infection increased over time for each period (n=3 waves) of pandemic (mean number of patients per month during the first wave 332, 322 during the 2nd and 595 during the third one). In the medical history, the most associated concomitant disease was chronic respiratory diseases. Patients hospitalized during the third wave presented a higher incidence of pulmonary involvement (10.2% compared to 7% and 6.5% during respectively the first and second wave). The highest incidence of Pediatric Inflammatory Multisystem Syndrome (PIMS) was observed during the first and second wave (4.2% in the 1st and 2nd wave compared to 2.3% during the 3rd one). Discussion This analysis highlighted the high incidence of hospitalized children in the Greater Paris Area during the third wave of COVID-19 pandemic corresponding to the Omicron Covid-19 variant, which is probably expression of a concomitant COVID-19 infection while a decreased incidence of PIMS complication was observed during the same period.